Optical glass, optical element and optical instrument

By rationally designing the components of optical glass, especially controlling the ratio of P2O5, Nb2O5, TiO2, BaO and Na2O, the problem of difficulty in producing high-refractive and high-dispersion optical glass with excellent intrinsic quality in the prior art is solved, and optical glass with high refractive index and high dispersion is achieved to meet the needs of high-performance optical instruments.

CN119569335APending Publication Date: 2025-03-07CDGM OPTICAL GLASS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311149928.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-07
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prior art is difficult to produce high refractive high dispersion optical glass with excellent intrinsic quality, especially when ensuring the refractive index between 1.86 and 1.93 and the Abbe number between 16 and 24.

Method used

By reasonably designing the components of the optical glass, the proportion of each component is controlled to achieve excellent optical performance.

Benefits of technology

It achieves high refractive index and high dispersion optical glass, with excellent intrinsic quality, meeting the needs of high-performance optical instruments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004436497300000171
    Figure BDA0004436497300000171
  • Figure BDA0004436497300000172
    Figure BDA0004436497300000172
  • Figure BDA0004436497300000191
    Figure BDA0004436497300000191
Patent Text Reader

Abstract

The invention provides optical glass, which comprises the following components in percentage by weight: 16 to 33 percent of P2O5; nb2O5: 40% to 55%; 1 to 13 percent of TiO2; 1 to 15% of BaO; and 0.5 to 15% of Na2O. Through reasonable component design, the optical glass obtained by the invention has excellent inherent quality while having expected refractive index and Abbe number, and meets the use of high-performance optical instruments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an optical glass, in particular to an optical glass with a refractive index of 1.86-1.93 and an Abbe number of 16-24, and an optical element and an optical instrument made of the optical glass. Background Art

[0002] In recent years, with the rapid development of optoelectronic information, digital display, surveillance and security, and vehicle-mounted imaging, the requirements for miniaturization, lightweight, and high performance have been put forward for optical components used in optical systems. High-refractive and high-dispersion optical glass can be coupled with low-dispersion optical glass to effectively eliminate chromatic aberration and secondary spectrum. At the same time, it can effectively shorten the total optical length of the lens and miniaturize the imaging system. Therefore, this type of glass has a wide range of applications. Under the same radius of curvature, the higher the refractive index of the glass, the larger the imaging field of view, which is conducive to reducing the number of optical components in optical instruments. With the development trend of miniaturization of optical instruments, the demand for high-refractive index glass is becoming more and more obvious.

[0003] Chinese patent CN101792258A discloses a high-refractive and high-dispersion optical glass with a refractive index of 1.70-2.20 and an Abbe number of 10-40, which contains 40-85 mol% of TeO2. This glass is prone to volatilization streaks during the production process due to the large amount of TeO2 contained, which is not conducive to the formation of optical glass with excellent intrinsic quality. Chinese patent CN1204073C discloses a high-refractive and high-dispersion optical glass with a refractive index of more than 1.88 and an Abbe number of 22-28, which contains 15-25wt% of SiO2, and its meltability needs to be improved. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide an optical glass with excellent intrinsic quality, a refractive index of 1.86-1.93 and an Abbe number of 16-24.

[0005] The technical solution adopted by the present invention to solve the technical problem is:

[0006] The optical glass comprises, expressed in weight percentage, 16-33% P2O5, 40-55% Nb2O5, 1-13% TiO2, 1-15% BaO and 0.5-15% Na2O.

[0007] Furthermore, the optical glass, expressed in weight percentage, further comprises: CaO: 0-8%; and / or MgO: 0-5%; and / or SrO: 0-5%; and / or ZnO: 0-8%; and / or Li2O: 0-5%; and / or K2O: 0-5%; and / or Ln2O3: 0-5%; and / or SiO2: 0-5%; and / or B2O3: 0-5%; and / or Al 2O3: 0-3%; and / or WO3: 0-3%; and / or ZrO2: 0-5%; and / or Bi2O3: 0-3%; and / or TeO2: 0-5%; and / or clarifier: 0-1%, wherein Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3, and the clarifier is one or more of Sb2O3, SnO2, and CeO2.

[0008] Optical glass, whose components are expressed in weight percentage, is composed of P2O5: 16-33%; Nb2O5: 40-55%; TiO2: 1-13%; BaO: 1-15%; Na2O: 0.5-15%; CaO: 0-8%; MgO: 0-5%; SrO: 0-5%; ZnO: 0-8%; Li2O: 0-5%; K2O: 0-5%; Ln2O3: 0-5%; SiO2: 0~5%; B2O3: 0~5%; Al2O3: 0~3%; WO3: 0~3%; ZrO2: 0~5%; Bi2O3: 0~3%; TeO2: 0~5%; clarifier: 0~1%, wherein the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3, and the clarifier is one or more of Sb2O3, SnO2, and CeO2.

[0009] Furthermore, the optical glass has components expressed in weight percentage, wherein:

[0010] (B2O3+WO3+Bi2O3) / ZnO is less than 2.0, preferably (B2O3+WO3+Bi2O3) / ZnO is less than 1.0, more preferably (B2O3+WO3+Bi2O3) / ZnO is less than 0.5, and further preferably (B2O3+WO3+Bi2O3) / ZnO is less than 0.2.

[0011] Furthermore, the optical glass, whose components are expressed in weight percentage, wherein: ZnO / BaO is less than 3.0, preferably ZnO / BaO is 0.05-2.0, more preferably ZnO / BaO is 0.1-1.5, and further preferably ZnO / BaO is 0.2-0.8.

[0012] Furthermore, the optical glass has components expressed in weight percentage, wherein:

[0013] (B2O3+Li2O+K2O) / ZnO is less than 2.0, preferably (B2O3+Li2O+K2O) / ZnO is less than 1.0, more preferably (B2O3+Li2O+K2O) / ZnO is less than 0.5, and further preferably (B2O3+Li2O+K2O) / ZnO is less than 0.2.

[0014] Furthermore, the optical glass has components expressed in weight percentage, wherein:

[0015] (P2O5+BaO) / (ZnO+CaO) is above 2.0, preferably (P2O5+BaO) / (ZnO+CaO) is 3.0 to 20.0, more preferably (P2O5+BaO) / (ZnO+CaO) is 5.0 to 15.0, and further preferably (P2O5+BaO) / (ZnO+CaO) is 8.0 to 12.0.

[0016] Furthermore, the optical glass has components expressed in weight percentage, wherein:

[0017] (Na2O+K2O) / Nb2O5 is 0.05 to 0.45, preferably (Na2O+K2O) / Nb2O5 is 0.1 to 0.4, more preferably (Na2O+K2O) / Nb2O5 is 0.1 to 0.3, and further preferably (Na2O+K2O) / Nb2O5 is 0.1 to 0.25.

[0018] Furthermore, the optical glass has components expressed in weight percentage, wherein:

[0019] (BaO+K2O+ZnO) / (Na2O+CaO) is 0.1 to 8.0, preferably (BaO+K2O+ZnO) / (Na2O+CaO) is 0.2 to 5.0, more preferably (BaO+K2O+ZnO) / (Na2O+CaO) is 0.3 to 2.5, and further preferably (BaO+K2O+ZnO) / (Na2O+CaO) is 0.5 to 1.5.

[0020] Furthermore, the optical glass has components expressed in weight percentage, wherein:

[0021] (TiO2+K2O) / P2O5 is 0.05 to 0.8, preferably (TiO2+K2O) / P2O5 is 0.1 to 0.6, more preferably (TiO2+K2O) / P2O5 is 0.1 to 0.5, and further preferably (TiO2+K2O) / P2O5 is 0.15 to 0.4.

[0022] Furthermore, the optical glass has components expressed in weight percentage, wherein:

[0023] (Ln2O3+Li2O+K2O+WO3+Bi2O3) / TiO2 is less than 0.8, preferably

[0024] (Ln2O3+Li2O+K2O+WO3+Bi2O3) / TiO2 is less than 0.5, more preferably (Ln2O3+Li2O+K2O+WO3+Bi2O3) / TiO2 is less than 0.3, and further preferably (Ln2O3+Li2O+K2O+WO3+Bi2O3) / TiO2 is less than 0.1, and the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3.

[0025] Furthermore, the optical glass has components expressed in weight percentage, wherein:

[0026] (WO3+TiO2) / Nb2O5 is 0.02 to 0.3, preferably (WO3+TiO2) / Nb2O5 is 0.05 to 0.25, more preferably (WO3+TiO2) / Nb2O5 is 0.05 to 0.2, and further preferably (WO3+TiO2) / Nb2O5 is 0.07 to 0.17.

[0027] Furthermore, the components of the optical glass are expressed in weight percentage, wherein: ZnO / TiO2 is less than 3.0, preferably ZnO / TiO2 is 0.01-2.0, more preferably ZnO / TiO2 is 0.1-1.5, and further preferably ZnO / TiO2 is 0.2-0.8.

[0028] Furthermore, the components of the optical glass are expressed in weight percentage, wherein: TiO2 / BaO is 0.2-8.0, preferably TiO2 / BaO is 0.3-5.0, more preferably TiO2 / BaO is 0.5-3.0, and further preferably TiO2 / BaO is 0.6-1.5.

[0029] Furthermore, the components of the optical glass are expressed in weight percentage, wherein: ZnO / (Na2O+TiO2) is less than 2.0, preferably ZnO / (Na2O+TiO2) is 0.01-1.5, more preferably ZnO / (Na2O+TiO2) is 0.05-0.8, and further preferably ZnO / (Na2O+TiO2) is 0.05-0.4.

[0030] Furthermore, the components of the optical glass are expressed in weight percentage, wherein: TiO2 / CaO is 0.5-10.0, preferably TiO2 / CaO is 1.0-8.0, more preferably TiO2 / CaO is 2.0-7.0, and further preferably TiO2 / CaO is 2.5-6.0.

[0031] Furthermore, the optical glass, its components are expressed in weight percentage, wherein: P2O5: 20-30%, preferably P2O5: 22-28%; and / or Nb2O5: 45-55%, preferably Nb2O5: 46-53%; and / or TiO2: 3-10%, preferably TiO2: 4-8%; and / or BaO: 2-12%, preferably BaO: 3-9%; and / or Na2O: 3-12%, preferably Na2 O: 6-10%; and / or CaO: greater than 0 but less than or equal to 6%, preferably CaO: 1-4%; and / or MgO: 0-3%, preferably MgO: 0-1%; and / or SrO: 0-3%, preferably SrO: 0-1%; and / or ZnO: greater than 0 but less than or equal to 6%, preferably ZnO: 1-4%; and / or Li2O: 0-3%, preferably Li2O: 0-1%; and / or K2O: 0-3%, preferably K2 O: 0-1%; and / or Ln2O3: 0-3%, preferably Ln2O3: 0-1%; and / or SiO2: 0-3%, preferably SiO2: 0-1%; and / or B2O3: 0-3%, preferably B2O3: 0-1%; and / or Al2O3: 0-2%, preferably Al2O3: 0-1%; and / or WO3: 0-2%, preferably WO3: 0-1%; and / or ZrO2: 0-3%, preferably ZrO2: 0~1%; and / or Bi2O3: 0~2%, preferably Bi2O3: 0~1%; and / or TeO2: 0~3%, preferably TeO2: 0~1%; and / or clarifier: 0~0.5%, preferably clarifier: 0~0.1%, the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, Lu2O3, and the clarifier is one or more of Sb2O3, SnO2, and CeO2.

[0032] Furthermore, the optical glass does not contain MgO, SrO, Li2O, K2O, Ln2O3, B2O3, Al2O3, WO3, ZrO2, Bi2O3, TeO2, and / or clarifier, and the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3, and the clarifier is one or more of Sb2O3, SnO2, and CeO2.

[0033] Furthermore, the refractive index n of the optical glass is d 1.86 to 1.93, preferably 1.87 to 1.92, more preferably 1.88 to 1.91; Abbe number ν d It is 16-24, preferably 17-23, and more preferably 18-22.

[0034] Furthermore, the thermal expansion coefficient α of the optical glass is 100 / 300℃ 95×10 -7 / K or less, preferably 90×10 -7 / K or less, more preferably 85×10 -7 / K or less; and / or acid resistance stability D A 2 or more, preferably 1; and / or water resistance stability D W Two or more types, preferably one type; and / or relative partial dispersion P g,F 0.58 to 0.72, preferably 0.60 to 0.68, more preferably 0.63 to 0.66; and / or relative partial dispersion deviation value ΔP g,F is 0.08 or less, preferably 0.01 to 0.06, more preferably 0.02 to 0.05; and / or the transition temperature T g 670°C or less, preferably 660°C or less, more preferably 650°C or less; and / or abrasion degree F A 230 to 270, preferably 240 to 265, more preferably 245 to 260; and / or density ρ is 3.90 g / cm 3 Below, preferably 3.80g / cm 3 Below, more preferably 3.70g / cm 3 Below; and / or 70 440nm or less, preferably λ 70 430nm or less, preferably λ 70 is 425nm or less; and / or λ5 is 400nm or less, preferably λ5 is 390nm or less, more preferably λ5 is 385nm or less; and / or weather resistance CR is 2 or more, preferably 1; and / or Young's modulus E is 8000×10 7 Pa or more, preferably 9000×10 7 Pa or more, more preferably 9500×10 7 Pa or more; and / or the bubble degree is A grade or more, preferably A0 grade or more, more preferably A 00 class.

[0035] The glass preform is made of the above optical glass.

[0036] The optical element is made of the above optical glass, or made of the above glass preform.

[0037] An optical instrument containing the above optical glass or the above optical element.

[0038] The beneficial effect of the present invention is that, through reasonable component design, the optical glass obtained by the present invention has the desired refractive index and Abbe number and has excellent intrinsic quality, which meets the use of high-performance optical instruments. DETAILED DESCRIPTION

[0039] The following will describe the embodiments of the optical glass of the present invention in detail, but the present invention is not limited to the following embodiments, and can be implemented by appropriate changes within the scope of the purpose of the present invention. In addition, although there are appropriate omissions of descriptions of the repeated descriptions, the gist of the invention will not be limited thereby, and in the following content, the optical glass of the present invention is sometimes referred to as glass.

[0040] [Optical glass]

[0041] The following is an explanation of the range of each component (ingredient) of the optical glass of the present invention. In the present invention, unless otherwise specified, the content and total content of each component are all expressed in weight percentage (wt%), that is, the content and total content of each component are expressed in weight percentage relative to the total amount of glass material converted into oxide composition. Here, the "composition converted into oxide" means that when the oxides, complex salts and hydroxides used as raw materials for the optical glass components of the present invention decompose and transform into oxides during melting, the total amount of the oxide material is taken as 100%.

[0042] Unless otherwise specified in specific circumstances, the numerical ranges listed in the present invention include upper and lower limits, "above" and "below" include endpoint values, and all integers and fractions included in the range, without being limited to the specific values ​​listed when the range is defined. "And / or" referred to herein is inclusive, for example, "A and / or B" means only A, or only B, or both A and B.

[0043] <Essential Components and Optional Components>

[0044] P2O5 is a network generator of the glass of the present invention. Compared with silicate glass, phosphate glass can be melted at a low temperature, which is beneficial to improve the light transmittance of the glass. If the content of P2O5 is too high, it is difficult for the glass to obtain a higher refractive index. Therefore, the content of P2O5 in the present invention is 16-33%, preferably 20-30%, and more preferably 22-28%.

[0045] Nb2O5 is a high refractive and high dispersion component that can increase the refractive index and devitrification resistance of glass and has the effect of reducing the relative partial dispersion (P g,F ) and relative partial dispersion deviation (ΔP g,F ), the above effect is obtained by containing more than 40% Nb2O5 in the present invention, and the lower limit of the content of Nb2O5 is preferably 45%, and the lower limit is more preferably 46%. If the content of Nb2O5 exceeds 55%, the thermal stability and chemical stability of the glass will decrease, and the light transmittance will decrease. Therefore, the upper limit of the content of Nb2O5 in the present invention is 55%, and the upper limit is preferably 53%.

[0046] TiO2 has high refractive and high dispersion properties, which can improve the chemical stability of glass and adjust the relative partial dispersion of glass (P g,F ) and relative partial dispersion deviation (ΔP g,F ), if its content is too high, the devitrification resistance and light transmittance of the glass will decrease. Therefore, the content of TiO2 is 1 to 13%, preferably 3 to 10%, and more preferably 4 to 8%.

[0047] BaO can improve the resistance to devitrification and hardness of glass, and reduce the temperature coefficient of refractive index and thermal expansion coefficient of glass. In the present invention, the above effects are obtained by containing more than 1% of BaO. Preferably, the content of BaO is more than 2%, and more preferably, the content of BaO is more than 3%. On the other hand, by making the content of BaO less than 15%, the reduction of chemical stability caused by excessive BaO content can be prevented. Therefore, the content of BaO is less than 15%, preferably, the content of BaO is less than 12%, and more preferably, the content of BaO is less than 9%.

[0048] In some embodiments, the ratio of TiO2 to BaO is controlled within the range of 0.2 to 8.0, which is beneficial to improving the chemical stability of the glass and reducing the thermal expansion coefficient of the glass. Therefore, TiO2 / BaO is preferably 0.2 to 8.0, and more preferably TiO2 / BaO is 0.3 to 5.0. Furthermore, controlling TiO2 / BaO within the range of 0.5 to 3.0 can further optimize the abrasiveness of the glass, making it easier for the glass to obtain the desired P g,F Value and ΔP g,F Therefore, it is more preferred that TiO2 / BaO is 0.5 to 3.0, and it is further preferred that TiO2 / BaO is 0.6 to 1.5.

[0049] CaO helps to adjust the optical constants of glass and improve the processing performance and weather resistance of glass, but when the content of CaO is too much, the anti-devitrification performance of glass will be deteriorated. Therefore, the content of CaO is 0 to 8%, preferably greater than 0 but less than or equal to 6%, and more preferably 1 to 4%.

[0050] In some embodiments, the ratio of TiO2 to CaO is controlled within the range of 0.5 to 10.0, which is beneficial to reducing the thermal expansion coefficient of the glass and optimizing the Young's modulus and abrasion resistance of the glass. Therefore, preferably TiO2 / CaO is 0.5 to 10.0, more preferably TiO2 / CaO is 1.0 to 8.0, further preferably TiO2 / CaO is 2.0 to 7.0, and further preferably TiO2 / CaO is 2.5 to 6.0.

[0051] SrO can adjust the refractive index and dispersion of glass, but if its content is too high, the chemical stability of the glass will decrease and the cost of the glass will also increase. Therefore, the content of SrO is 0-5%, preferably 0-3%, and more preferably 0-1%. In some embodiments, it is further preferred that SrO is not contained.

[0052] MgO is beneficial for reducing the density and melting temperature of glass, but when the MgO content is too high, the refractive index of the glass is difficult to meet the design requirements, and the anti-devitrification performance and stability of the glass are reduced. Therefore, the content of MgO is 0-5%, preferably 0-3%, and more preferably 0-1%. In some embodiments, it is further preferred that MgO is not contained.

[0053] ZnO can reduce the glass transition temperature and the melting temperature, improve the chemical stability of the glass, and reduce the high temperature viscosity of the glass. If the ZnO content is too high, the anti-crystallization performance of the glass will deteriorate, and devitrification will easily occur due to the low viscosity. Therefore, the content of ZnO in the present invention is 0-8%, preferably greater than 0 but less than or equal to 6%, and more preferably 1-4%.

[0054] In some embodiments, the ratio ZnO / (Na2O+TiO2) between the content of ZnO and the total content of Na2O and TiO2, Na2O+TiO2, is controlled to be below 2.0, which can improve the bubble degree of the glass while preventing the glass transition temperature from rising. Therefore, it is preferred that ZnO / (Na2O+TiO2) is below 2.0, and it is more preferred that ZnO / (Na2O+TiO2) is 0.01 to 1.5. Furthermore, controlling ZnO / (Na2O+TiO2) within the range of 0.05 to 0.8 can further optimize the abrasion resistance and weather resistance of the glass. Therefore, it is further preferred that ZnO / (Na2O+TiO2) is 0.05 to 0.8, and it is further preferred that ZnO / (Na2O+TiO2) is 0.05 to 0.4.

[0055] In some embodiments, the ratio (P2O5+BaO) / (ZnO+CaO) between the total content of P2O5 and BaO P2O5+BaO and the total content of ZnO and CaO ZnO+CaO is controlled to be above 2.0, which can improve the light transmittance of the glass while preventing the transition temperature from deteriorating. Therefore, it is preferred that (P2O5+BaO) / (ZnO+CaO) is above 2.0, and it is more preferred that (P2O5+BaO) / (ZnO+CaO) is 3.0 to 20.0. Furthermore, by controlling (P2O5+BaO) / (ZnO+CaO) within the range of 5.0 to 15.0, the Young's modulus and the bubble degree of the glass can be further optimized. Therefore, it is further preferred that (P2O5+BaO) / (ZnO+CaO) is 5.0 to 15.0, and it is further preferred that (P2O5+BaO) / (ZnO+CaO) is 8.0 to 12.0.

[0056] In some embodiments, controlling the ratio of ZnO content to BaO content ZnO / BaO to less than 3.0 is beneficial to improving the weather resistance of the glass. Therefore, it is preferred that ZnO / BaO is less than 3.0. Further, controlling ZnO / BaO within the range of 0.05 to 2.0 can also optimize the abrasiveness of the glass while lowering the transition temperature of the glass. Therefore, it is more preferred that ZnO / BaO is 0.05 to 2.0, further preferred that ZnO / BaO is 0.1 to 1.5, and further preferred that ZnO / BaO is 0.2 to 0.8.

[0057] In some embodiments, the ratio ZnO / TiO2 between the content of ZnO and the content of TiO2 is controlled to be below 3.0, which can optimize the abrasiveness and chemical stability of the glass and prevent the transition temperature of the glass from increasing. Therefore, ZnO / TiO2 is preferably below 3.0, more preferably ZnO / TiO2 is 0.01 to 2.0, further preferably ZnO / TiO2 is 0.1 to 1.5, and further preferably ZnO / TiO2 is 0.2 to 0.8.

[0058] Li2O can improve the melting property of glass and reduce the transition temperature. If its content is too high, the refractive index of glass is difficult to meet the design requirements and the chemical stability of glass is deteriorated. Therefore, the content of Li2O in the present invention is 0-5%, preferably 0-3%, and more preferably 0-1%. In some embodiments, it is further preferred that Li2O is not contained.

[0059] Na2O can improve the meltability and formability of glass and optimize the light transmittance of glass. If its content is too high, it will be detrimental to the thermal expansion coefficient and chemical stability of glass. Therefore, the content of Na2O is 0.5-15%, preferably 3-12%, and more preferably 6-10%.

[0060] K2O has the effect of improving the thermal stability and melting property of glass, but if its content is too high, the resistance to devitrification of glass will decrease. Therefore, the content of K2O is 0 to 5%, preferably 0 to 3%, and more preferably 0 to 1%. In some embodiments, it is further preferred that K2O is not contained.

[0061] In some embodiments, the ratio of the total content of Na2O and K2O Na2O+K2O to the content of Nb2O5 (Na2O+K2O) / Nb2O5 is controlled within the range of 0.05 to 0.45, which is beneficial for the glass to obtain high refractive index, high dispersion and desired P g,F Value and ΔP g,F Therefore, it is preferred that (Na2O+K2O) / Nb2O5 is 0.05-0.45, more preferably (Na2O+K2O) / Nb2O5 is 0.1-0.4, further preferably (Na2O+K2O) / Nb2O5 is 0.1-0.3, and further preferably (Na2O+K2O) / Nb2O5 is 0.1-0.25.

[0062] In some embodiments, the ratio of the total content of TiO2 and K2O (TiO2+K2O) to the content of P2O5 ((TiO2+K2O) / P2O5) is controlled within the range of 0.05 to 0.8, so that the glass has a desired P g,F Value and ΔP g,F Therefore, it is preferred that (TiO2+K2O) / P2O5 is 0.05 to 0.8, more preferably (TiO2+K2O) / P2O5 is 0.1 to 0.6, further preferably (TiO2+K2O) / P2O5 is 0.1 to 0.5, and further preferably (TiO2+K2O) / P2O5 is 0.15 to 0.4.

[0063] Ln2O3 (Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3) is a component that increases the refractive index of glass and is an optional component in the optical glass of the present invention. By controlling the content of Ln2O3 to less than 5%, it is possible to prevent the devitrification resistance of the glass from decreasing. Therefore, in the present invention, the content of Ln2O3 is 0 to 5%, preferably 0 to 3%, and more preferably 0 to 1%. In some embodiments, it is further preferred that Ln2O3 is not contained.

[0064] By containing SiO2 in phosphate glass, the glass grid can be made more compact, and the chemical stability and mechanical strength of the glass can be improved. However, the phosphate glass grid is not very compatible with SiO2, and when the SiO2 content is too high, phase separation is likely to occur. Therefore, the content of SiO2 in the present invention is 0-5%, preferably 0-3%, and more preferably 0-1%.

[0065] B2O3 has the effect of improving the thermal stability and melting property of glass, but when its content is high, the chemical stability and resistance to devitrification of glass decrease. Therefore, the content of B2O3 in the present invention is 0 to 5%, preferably 0 to 3%, and more preferably 0 to 1%. In some embodiments, it is further preferred that B2O3 is not contained.

[0066] In some embodiments, the ratio of the total content of B2O3, Li2O and K2O (B2O3+Li2O+K2O) to the content of ZnO (B2O3+Li2O+K2O) / ZnO is controlled to be below 2.0, so that the glass can obtain the desired P g,F Value and ΔP g,F The value and Young's modulus are increased while preventing the chemical stability and bubble degree of the glass from deteriorating. Therefore, it is preferred that (B2O3+Li2O+K2O) / ZnO is 2.0 or less, more preferably (B2O3+Li2O+K2O) / ZnO is 1.0 or less, further preferably (B2O3+Li2O+K2O) / ZnO is 0.5 or less, and further preferably (B2O3+Li2O+K2O) / ZnO is 0.2 or less.

[0067] In some embodiments, the ratio of the total content of BaO, K2O and ZnO BaO+K2O+ZnO to the total content of Na2O and CaO Na2O+CaO (BaO+K2O+ZnO) / (Na2O+CaO) is within the range of 0.1 to 8.0, which is beneficial to reducing the density and thermal expansion coefficient of the glass. Therefore, it is preferred that (BaO+K2O+ZnO) / (Na2O+CaO) is 0.1 to 8.0, and it is more preferred that (BaO+K2O+ZnO) / (Na2O+CaO) is 0.2 to 5.0. Furthermore, controlling (BaO+K2O+ZnO) / (Na2O+CaO) within the range of 0.3 to 2.5 can further optimize the abrasion resistance and weather resistance of the glass. Therefore, it is more preferred that (BaO+K2O+ZnO) / (Na2O+CaO) is 0.3 to 2.5, and it is further preferred that (BaO+K2O+ZnO) / (Na2O+CaO) is 0.5 to 1.5.

[0068] Al2O3 can improve the chemical stability of glass, but when its content exceeds 3%, the melting property and light transmittance of glass deteriorate. Therefore, the content of Al2O3 in the present invention is 0 to 3%, preferably 0 to 2%, and more preferably 0 to 1%. In some embodiments, it is further preferred that Al2O3 is not contained.

[0069] WO3 is an optional component that can adjust the optical constants and devitrification resistance of glass, but when its content is high, the transmittance and anti-devitrification performance of glass decrease. Therefore, the content of WO3 is 0 to 3%, preferably 0 to 2%, and more preferably 0 to 1%. In some embodiments, it is further preferred that WO3 is not contained.

[0070] In some embodiments, the ratio of the total content of WO3 and TiO2, WO3+TiO2, to the content of Nb2O5, (WO3+TiO2) / Nb2O5, is controlled within the range of 0.02 to 0.3, which is beneficial to reducing the density of the glass and optimizing the Young's modulus and abrasion resistance of the glass. Therefore, preferably (WO3+TiO2) / Nb2O5 is 0.02 to 0.3, more preferably (WO3+TiO2) / Nb2O5 is 0.05 to 0.25, further preferably (WO3+TiO2) / Nb2O5 is 0.05 to 0.2, and further preferably (WO3+TiO2) / Nb2O5 is 0.07 to 0.17.

[0071] The right amount of ZrO2 can increase the mechanical strength and hardness of glass, improve the anti-crystallization performance of glass, and adjust the P g,F Value and ΔP g,F However, ZrO2 is difficult to melt in phosphate glass, and excessive ZrO2 content will lead to difficulty in sintering. Therefore, the content of ZrO2 in the present invention is 0-5%, preferably 0-3%, and more preferably 0-1%. In some embodiments, it is further preferred that ZrO2 is not contained.

[0072] Bi2O3 can increase the refractive index of glass, but Bi2O3 has a high density, which is not conducive to the lightweight design of glass. Therefore, the content of Bi2O3 in the present invention is 0-3%, preferably 0-2%, and more preferably 0-1%. In some embodiments, it is further preferred that Bi2O3 is not contained.

[0073] In some embodiments, the ratio of the total content of B2O3, WO3 and Bi2O3 (B2O3+WO3+Bi2O3) / ZnO to the content of ZnO is controlled to be below 2.0, which is beneficial for the glass to obtain the desired P g,F Value and ΔP g,FWhile optimizing the light transmittance and bubble degree of the glass, the density of the glass is prevented from increasing. Therefore, it is preferred that (B2O3+WO3+Bi2O3) / ZnO is less than 2.0, more preferably (B2O3+WO3+Bi2O3) / ZnO is less than 1.0, further preferably (B2O3+WO3+Bi2O3) / ZnO is less than 0.5, and further preferably (B2O3+WO3+Bi2O3) / ZnO is less than 0.2.

[0074] In some embodiments, the ratio of the total content of Ln2O3, Li2O, K2O, WO3 and Bi2O3 (Ln2O3+Li2O+K2O+WO3+Bi2O3) / TiO2 to the content of TiO2 is controlled to be below 0.8, and the glass has a desired P g,F Value and ΔP g,F value, while optimizing the chemical stability and bubble degree of the glass.

[0075] (Ln2O3+Li2O+K2O+WO3+Bi2O3) / TiO2 is 0.8 or less, and more preferably

[0076] (Ln2O3+Li2O+K2O+WO3+Bi2O3) / TiO2 is less than 0.5, and it is further preferred that (Ln2O3+Li2O+K2O+WO3+Bi2O3) / TiO2 is less than 0.3, and it is further preferred that (Ln2O3+Li2O+K2O+WO3+Bi2O3) / TiO2 is less than 0.1.

[0077] TeO2 is an optional component that increases the refractive index of glass and lowers the transition temperature of glass. When its content is too high, it is easy to react with platinum utensils, reducing the service life of platinum utensils, easily causing platinum particles to enter the glass, reducing the transmittance of the glass, and easily generating volatilization streaks, reducing the intrinsic quality of the glass. Therefore, the content of TeO2 is limited to 5% or less, preferably 3% or less, and more preferably 1% or less. In some embodiments, it is further preferred that TeO2 is not contained.

[0078] In the present invention, by containing 0-1% of one or more components of Sb2O3, SnO2, and CeO2 as a clarifier, the clarification effect of the glass can be improved, and the bubble degree of the glass can be improved. The content of the clarifier is preferably 0-0.5%, and the content of the clarifier is more preferably 0-0.1%. Since the component types and contents of the optical glass of the present invention are reasonably designed and its bubble degree is excellent, it is further preferred in some embodiments that no clarifier is contained. When the content of Sb2O3 exceeds 1%, the glass tends to have reduced clarification performance. At the same time, due to its strong oxidizing effect, it promotes the corrosion of platinum or platinum alloy vessels for melting glass and the deterioration of the forming mold. Therefore, the present invention preferably contains 0-1% of Sb2O3, more preferably 0-0.5%, further preferably 0-0.1%, and further preferably does not contain Sb2O3. SnO2 can also be used as a clarifier, but when its content exceeds 1%, the tendency of glass coloring increases, or when the glass is heated, softened, and molded again, Sn will become the starting point of crystal nucleation, resulting in a tendency to devitrification. Therefore, the content of SnO2 in the present invention is preferably 0-1%, more preferably 0-0.5%, further preferably 0-0.1%, and further preferably no SnO2. The function and content ratio of CeO2 are consistent with those of SnO2, and its content is preferably 0-1%, more preferably 0-0.5%, further preferably 0-0.1%, and further preferably no CeO2.

[0079] <Components that should not be contained>

[0080] In the glass of the present invention, even if oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo are contained alone or in combination in small amounts, the glass will be colored and absorption will occur at specific wavelengths in the visible light region, thereby weakening the property of the present invention of improving the visible light transmittance. Therefore, it is preferably substantially free of oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo, especially for optical glasses that require transmittance at wavelengths in the visible light region.

[0081] The oxides of Th, Cd, Tl, Os, Be and Se have a tendency to be controlled in recent years as harmful chemical substances, and environmental protection measures are necessary not only in the manufacturing process of glass, but also in the processing process and the disposal after productization. Therefore, in the case of paying attention to the impact on the environment, it is preferred that they are not actually contained except for being inevitably mixed in. Thus, the optical glass does not actually contain substances that pollute the environment. Therefore, even if special environmental countermeasures are not taken, the optical glass of the present invention can be manufactured, processed and discarded.

[0082] In order to achieve environmental friendliness, the optical glass of the present invention preferably does not contain As2O3 and PbO.

[0083] The "does not contain" and "0%" recorded in this article mean that the compound, molecule or element is not intentionally added as a raw material to the optical glass of the present invention; however, as raw materials and / or equipment for producing optical glass, there will be certain impurities or components that are not intentionally added, which will be contained in a small amount or trace amount in the final optical glass, and this situation is also within the scope of protection of the patent of this invention.

[0084] Next, the properties of the optical glass of the present invention will be described.

[0085] <Refractive Index and Abbe Number>

[0086] The refractive index of optical glass (n d ) and the Abbe number (ν d ) Tested according to the method specified in GB / T 7962.1-2010.

[0087] In some embodiments, the refractive index (n d ) has a lower limit of 1.86, a preferred lower limit is 1.87, and a more preferred lower limit is 1.88.

[0088] In some embodiments, the refractive index (n d ) has an upper limit of 1.93, a preferred upper limit of 1.92, and a more preferred upper limit of 1.91.

[0089] In some embodiments, the Abbe number (ν d ) has a lower limit of 16, a preferred lower limit of 17, and a more preferred lower limit of 18.

[0090] In some embodiments, the Abbe number (ν d ) has an upper limit of 24, a preferred upper limit of 23, and a more preferred upper limit of 22.

[0091] <Coefficient of Thermal Expansion>

[0092] Thermal expansion coefficient of optical glass (α 100 / 300℃ ) Test data at 100-300℃ according to the method specified in GB / T7962.16-2010.

[0093] In some embodiments, the thermal expansion coefficient (α 100 / 300℃ ) is 95×10 -7 / K or less, preferably 90×10 -7 / K or less, more preferably 85×10 -7 / K or less.

[0094] <Acid resistance stability>

[0095] Acid resistance stability of optical glass (DA ) (Powder method) Tested in accordance with the method specified in GB / T 17129.

[0096] In some embodiments, the acid resistance stability (D A ) is 2 or more types, preferably 1 type.

[0097] <Water resistance stability>

[0098] Water resistance stability of optical glass (D W ) (Powder method) Tested in accordance with the method specified in GB / T 17129.

[0099] In some embodiments, the water resistance stability (D W ) is 2 or more types, preferably 1 type.

[0100] <Relative partial dispersion and relative partial dispersion deviation value>

[0101] The relative partial dispersion (P g,F ) and relative partial dispersion deviation (ΔP g,F ) origin.

[0102] The relative partial dispersion for wavelengths x and y is expressed by the following equation (1):

[0103] P x,y =(n x -n y ) / (n F -n C ) (1)

[0104] According to the Abbe number formula, for most so-called "normal glasses" (H-K6 and F4 are selected as "normal glasses" below), the following formula (2) is valid:

[0105] P x,y =m x,y ·v d +b x,y (2)

[0106] This linear relationship is based on P x,y is the vertical coordinate, v d It is represented by the horizontal axis, where m x,y is the slope, b x,y is the intercept.

[0107] As is known to all, the correction of the secondary spectrum, i.e. the achromatization of more than two wavelengths, requires at least one glass that does not conform to the above formula (2) (i.e. its P x,y The deviation value deviates from Abbe's empirical formula), and its deviation value is expressed as ΔP x,yIf it is expressed, then each P x,y -v d The point is shifted by ΔP relative to the "normal line" that conforms to the above formula (2) x,y Quantity, so that the ΔP of each glass x,y The value can be obtained using the following formula (3):

[0108] P x,y =m x,y ·v d +b x,y +ΔP x,y (3)

[0109] Therefore, ΔP x,y It quantitatively represents the deviation characteristics of special dispersion compared with "normal glass".

[0110] Therefore, the relative partial dispersion (P g,F ) and relative partial dispersion deviation (ΔP g,F ) is calculated as follows (4) and (5):

[0111] P g,F =(n g -n F ) / (n F -n C ) (4)

[0112] ΔP g,F =P g,F -0.6457+0.001703v d (5)

[0113] In some embodiments, the relative partial dispersion (P g,F ) has a lower limit of 0.58, a preferred lower limit of 0.60, and a more preferred lower limit of 0.63.

[0114] In some embodiments, the relative partial dispersion (P g,F ) has an upper limit of 0.72, a preferred upper limit of 0.68, and a more preferred upper limit of 0.66.

[0115] In some embodiments, the relative partial dispersion deviation value (ΔP g,F ) has a lower limit of 0.01, and a preferred lower limit is 0.02.

[0116] In some embodiments, the relative partial dispersion deviation value (ΔP g,F ) has an upper limit of 0.08, a preferred upper limit of 0.06, and a more preferred upper limit of 0.05.

[0117] <Transition Temperature>

[0118] Transition temperature of optical glass (T g ) The test shall be carried out in accordance with the method specified in GB / T7962.16-2010.

[0119] In some embodiments, the transition temperature (T g ) is 670°C or lower, preferably 660°C or lower, and more preferably 650°C or lower.

[0120] <Abrasion>

[0121] Abrasiveness of optical glass (F A ) refers to the value obtained by multiplying the ratio of the wear volume of the sample to the wear volume (volume) of the standard sample (H-K9 glass) under exactly the same conditions by 100, and is expressed by the following formula:

[0122] F A =V / V0×100=(W / ρ) / (W0 / ρ0)×100

[0123] Where: V—volume wear of the sample being tested;

[0124] V0—Volume loss of standard sample;

[0125] W—mass wear loss of the sample being tested;

[0126] W0—standard sample mass wear;

[0127] ρ—density of the sample being tested;

[0128] ρ0—standard sample density.

[0129] In some embodiments, the abrasiveness (F A ) has a lower limit of 230, a preferred lower limit of 240, and a more preferred lower limit of 245.

[0130] In some embodiments, the abrasiveness (F A ) has an upper limit of 270, a preferred upper limit of 265, and a more preferred upper limit of 260.

[0131] <density>

[0132] The density (ρ) is tested according to the method specified in GB / T7962.20-2010.

[0133] In some embodiments, the density (ρ) of the optical glass of the present invention is 3.90 g / cm 3 Below, preferably 3.80g / cm 3 Below, more preferably 3.70g / cm 3 the following.

[0134] <Color>

[0135] The short-wave transmission spectrum characteristics of the glass of the present invention are expressed by the coloration (λ 70 and λ5). 70 Refers to the wavelength when the glass transmittance reaches 70%. 70 The measurement is to use a glass with a thickness of 10±0.1mm and two opposite planes parallel to each other and optically polished, and measure the spectral transmittance in the wavelength range from 280nm to 700nm and the wavelength at which the transmittance is 70%. The so-called spectral transmittance or transmittance is the wavelength at which the incident intensity I is perpendicular to the above surface of the glass. in Light of intensity I passes through the glass and emerges from a plane out The light of the case through I out / I in The amount expressed by λ also includes the transmittance of the surface reflection loss on the above surfaces of the glass. The higher the refractive index of the glass, the greater the surface reflection loss. Therefore, in high refractive index glass, λ 70 A small value of means that the glass itself is less colored and has a high light transmittance.

[0136] In some embodiments, the λ of the optical glass of the present invention is 70 440nm or less, preferably λ 70 430nm or less, preferably λ 70 Below 425nm.

[0137] In some embodiments, the λ5 of the optical glass of the present invention is 400 nm or less, preferably λ5 is 390 nm or less, and more preferably λ5 is 385 nm or less.

[0138] <Weather resistance>

[0139] The test method for weather resistance (CR) of optical glass is as follows: place the sample in a test box with a saturated water vapor environment of 90% relative humidity, alternately cycle every 1 hour at 40-50°C, and cycle for 15 cycles. The weather resistance category is divided according to the change in turbidity before and after the sample is placed. The weather resistance classification is shown in Table 1:

[0140] Table 1.

[0141]

[0142] In some embodiments, the weather resistance (CR) of the optical glass of the present invention is Class 2 or higher, preferably Class 1.

[0143] <Young's modulus>

[0144] Young's modulus (E) is calculated using the following formula by ultrasonic testing of its longitudinal wave velocity and transverse wave velocity.

[0145]

[0146] G=V S 2 ρ

[0147] Where: E is Young's modulus, Pa;

[0148] G is the shear modulus, Pa;

[0149] V T is the shear wave velocity, m / s;

[0150] V S is the longitudinal wave velocity, m / s;

[0151] ρ is the glass density, g / cm 3 .

[0152] In some embodiments, the Young's modulus (E) of the optical glass of the present invention is 8000×10 7 Pa or more, preferably 9000×10 7 Pa or more, more preferably 9500×10 7 Pa or above.

[0153] <Bubble Degree>

[0154] The bubble degree of optical glass is tested according to the method specified in GB / T7962.8-2010.

[0155] In some embodiments, the bubble degree of the optical glass of the present invention is above grade A, preferably above grade A0, and more preferably above grade A1. 00 class.

[0156] [Method for producing optical glass]

[0157] The manufacturing method of the optical glass of the present invention is as follows: the glass of the present invention is produced by conventional raw materials and processes, including but not limited to using oxides, hydroxides, complex salts (such as carbonates, nitrates, sulfates, phosphates, metaphosphates, etc.), boric acid, etc. as raw materials, and after mixing according to conventional methods, the prepared furnace materials are put into a melting furnace (such as platinum or platinum alloy crucible) at 1050-1250°C, preferably 1100-1200°C for melting, and after clarification and homogenization, a homogeneous molten glass without bubbles and undissolved substances is obtained, and the molten glass is cast in a mold and annealed. Those skilled in the art can appropriately select raw materials, process methods and process parameters according to actual needs.

[0158] [Glass preforms and optical components]

[0159] The prepared optical glass can be used to make a glass preform by means of direct drop molding, grinding, or compression molding such as hot press molding. That is, the molten optical glass can be directly precision drop molded into a glass precision preform, or the glass preform can be made by mechanical processing such as grinding and grinding, or the preform for compression molding made of the optical glass can be made by hot press molding and then grinding. It should be noted that the means for preparing the glass preform are not limited to the above means.

[0160] As described above, the optical glass of the present invention is useful for various optical elements and optical designs, and it is particularly preferred to form a preform from the optical glass of the present invention and use the preform to perform re-hot pressing, precision stamping, etc. to produce optical elements such as lenses and prisms.

[0161] The glass preform and optical element of the present invention are both formed of the optical glass of the present invention. The glass preform of the present invention has the excellent properties of optical glass; the optical element of the present invention has the excellent properties of optical glass, and can provide various optical elements such as lenses and prisms with high optical value.

[0162] Examples of the lens include various lenses having spherical or aspherical lens surfaces, such as a concave meniscus lens, a convex meniscus lens, a biconvex lens, a biconcave lens, a plano-convex lens, and a plano-concave lens.

[0163] [Optical instruments]

[0164] The optical element formed by the optical glass of the present invention can be used to manufacture optical instruments such as photographic equipment, video equipment, projection equipment, display equipment, vehicle-mounted equipment and monitoring equipment.

[0165] Example

[0166] <Optical Glass Example>

[0167] In order to further clearly illustrate and describe the technical solution of the present invention, the following non-limiting examples are provided.

[0168] This embodiment adopts the above optical glass manufacturing method to obtain optical glasses having the compositions shown in Tables 2 to 4. In addition, the properties of each glass are measured by the testing method described in the present invention, and the measurement results are shown in Tables 2 to 4.

[0169] Table 2.

[0170]

[0171]

[0172] Table 3.

[0173]

[0174]

[0175]

[0176] Table 4.

[0177]

[0178]

[0179]

[0180] <Glass Preform Example>

[0181] The glass obtained from optical glass examples 1 to 21# is used, for example, by grinding processing, or by molding methods such as hot pressing, precision stamping, etc., to make preforms of various lenses, prisms, etc., such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses.

[0182] <Optical Element Embodiment>

[0183] The preforms obtained in the above-mentioned glass preform embodiments are annealed to reduce the internal stress of the glass and fine-tune the refractive index so that the optical properties such as the refractive index reach the desired values.

[0184] Next, each preform is ground and polished to produce various lenses and prisms such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses. The surface of the obtained optical element may be coated with an anti-reflection film.

[0185] <Optical Instrument Embodiment>

[0186] The optical element obtained by the above-mentioned optical element embodiment is optically designed to form an optical component or optical assembly by using one or more optical elements, and can be used in, for example, imaging equipment, sensors, microscopes, medical technology, digital projection, communications, optical communication technology / information transmission, optics / lighting in the automotive field, lithography technology, excimer lasers, wafers, computer chips, and integrated circuits and electronic devices including such circuits and chips.

Claims

1. Optical glass, characterized in that: Its components are expressed in weight percentage and contain: P2O5: 16-33%; Nb2O5: 40-55%; TiO2: 1-13%; BaO: 1-15%; Na2O: 0.5-15%.

2. The optical glass according to claim 1, characterized in that: Its components, expressed in weight percentage, also contain: CaO: 0-8%; and / or MgO: 0-5%; and / or SrO: 0-5%; and / or ZnO: 0-8%; and / or Li2O: 0-5%; and / or K2O: 0-5%; and / or Ln2O3: 0-5%; and / or SiO2: 0-5%; and / or B2O3: 0-5%; and / or Al2O3: 0-3%; and / or WO3: 0-3%; and / or ZrO2: 0-5%; and / or Bi2O3: 0-3%; and / or TeO2: 0-5%; and / or clarifier: 0-1%, wherein the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3, and the clarifier is one or more of Sb2O3, SnO2, and CeO2.

3. Optical glass, characterized in that: Its components, expressed in weight percentage, are P2O5: 16-33%; Nb2O5: 40-55%; TiO2: 1-13%; BaO: 1-15%; Na2O: 0.5-15%; CaO: 0-8%; MgO: 0-5%; SrO: 0-5%; ZnO: 0~8%; Li2O: 0~5%; K2O: 0~5%; Ln2O3: 0~5%; SiO2: 0~5%; B2O3: 0~5%; Al2O3: 0~3%; WO3: 0~3%; ZrO2: 0~5%; Bi2O3: 0~3%; TeO2: 0~5%; Clarifier: 0-1% composition, the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, Lu2O3, and the clarifier is one or more of Sb2O3, SnO2, CeO2.

4. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: (B2O3+WO3+Bi2O3) / ZnO is less than 2.0, preferably (B2O3+WO3+Bi2O3) / ZnO is less than 1.0, more preferably (B2O3+WO3+Bi2O3) / ZnO is less than 0.5, and further preferably (B2O3+WO3+Bi2O3) / ZnO is less than 0.

2.

5. The optical glass according to any one of claims 1 to 3, characterized in that: The components are expressed in weight percentage, wherein: ZnO / BaO is less than 3.0, preferably ZnO / BaO is 0.05-2.0, more preferably ZnO / BaO is 0.1-1.5, and further preferably ZnO / BaO is 0.2-0.

8.

6. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: (B2O3+Li2O+K2O) / ZnO is less than 2.0, preferably (B2O3+Li2O+K2O) / ZnO is less than 1.0, more preferably (B2O3+Li2O+K2O) / ZnO is less than 0.5, and further preferably (B2O3+Li2O+K2O) / ZnO is less than 0.

2.

7. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: (P2O5+BaO) / (ZnO+CaO) is greater than 2.0, preferably (P2O5+BaO) / (ZnO+CaO) is 3.0~20.0, more preferably (P2O5+BaO) / (ZnO+CaO) is 5.0~15.0, and further preferably (P2O5+BaO) / (ZnO+CaO) is 8.0~12.

0.

8. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: (Na2O+K2O) / Nb2O5 is 0.05-0.45, preferably (Na2O+K2O) / Nb2O5 is 0.1-0.4, more preferably (Na2O+K2O) / Nb2O5 is 0.1-0.3, and further preferably (Na2O+K2O) / Nb2O5 is 0.1-0.

25.

9. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: (BaO+K2O+ZnO) / (Na2O+CaO) is 0.1-8.0, preferably (BaO+K2O+ZnO) / (Na2O+CaO) is 0.2-5.0, more preferably (BaO+K2O+ZnO) / (Na2O+CaO) is 0.3-2.5, and further preferably (BaO+K2O+ZnO) / (Na2O+CaO) is 0.5-1.

5.

10. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: (TiO2+K2O) / P2O5 is 0.05-0.8, preferably (TiO2+K2O) / P2O5 is 0.1-0.6, more preferably (TiO2+K2O) / P2O5 is 0.1-0.5, and further preferably (TiO2+K2O) / P2O5 is 0.15-0.

4.

11. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: (Ln2O3+Li2O+K2O+WO3+Bi2O3) / TiO2 is less than 0.8, preferably (Ln2O3+Li2O+K2O+WO3+Bi2O3) / TiO2 is less than 0.5, more preferably (Ln2O3+Li2O+K2O+WO3+Bi2O3) / TiO2 is less than 0.3, and further preferably (Ln2O3+Li2O+K2O+WO3+Bi2O3) / TiO2 is less than 0.1, and the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3.

12. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: (WO3+TiO2) / Nb2O5 is 0.02-0.3, preferably (WO3+TiO2) / Nb2O5 is 0.05-0.25, more preferably (WO3+TiO2) / Nb2O5 is 0.05-0.2, and further preferably (WO3+TiO2) / Nb2O5 is 0.07-0.

17.

13. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: ZnO / TiO2 is less than 3.0, preferably ZnO / TiO2 is 0.01-2.0, more preferably ZnO / TiO2 is 0.1-1.5, and further preferably ZnO / TiO2 is 0.2-0.

8.

14. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: TiO2 / BaO is 0.2-8.0, preferably TiO2 / BaO is 0.3-5.0, more preferably TiO2 / BaO is 0.5-3.0, and further preferably TiO2 / BaO is 0.6-1.

5.

15. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: ZnO / (Na2O+TiO2) is less than 2.0, preferably ZnO / (Na2O+TiO2) is 0.01-1.5, more preferably ZnO / (Na2O+TiO2) is 0.05-0.8, and further preferably ZnO / (Na2O+TiO2) is 0.05-0.

4.

16. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: TiO2 / CaO is 0.5-10.0, preferably TiO2 / CaO is 1.0-8.0, more preferably TiO2 / CaO is 2.0-7.0, and further preferably TiO2 / CaO is 2.5-6.

0.

17. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: P2O5: 20-30%, preferably P2O5: 22-28%; and / or Nb2O5: 45-55%, preferably Nb2O5: 46-53%; and / or TiO2: 3-10%, preferably TiO2: 4-8%; and / or BaO: 2-12%, preferably BaO: 3-9%; and / or Na2O: 3-12%, preferably Na2O: 6-10%; and / or or CaO: greater than 0 but less than or equal to 6%, preferably CaO: 1-4%; and / or MgO: 0-3%, preferably MgO: 0-1%; and / or SrO: 0-3%, preferably SrO: 0-1%; and / or ZnO: greater than 0 but less than or equal to 6%, preferably ZnO: 1-4%; and / or Li2O: 0-3%, preferably Li2O: 0-1%; and / or K2O: 0-3%, preferably K2O: 0-1% ; and / or Ln2O3: 0-3%, preferably Ln2O3: 0-1%; and / or SiO2: 0-3%, preferably SiO2: 0-1%; and / or B2O3: 0-3%, preferably B2O3: 0-1%; and / or Al2O3: 0-2%, preferably Al2O3: 0-1%; and / or WO3: 0-2%, preferably WO3: 0-1%; and / or ZrO2: 0-3%, preferably ZrO2: 0-1 %; and / or Bi2O3: 0-2%, preferably Bi2O3: 0-1%; and / or TeO2: 0-3%, preferably TeO2: 0-1%; and / or clarifier: 0-0.5%, preferably clarifier: 0-0.1%, the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, Lu2O3, and the clarifier is one or more of Sb2O3, SnO2, and CeO2.

18. The optical glass according to any one of claims 1 to 3, characterized in that: Its components do not contain MgO; and / or do not contain SrO; and / or do not contain Li2O; and / or do not contain K2O; and / or do not contain Ln2O3; and / or do not contain B2O3; and / or do not contain Al2O3; and / or do not contain WO3; and / or do not contain ZrO2; and / or do not contain Bi2O3; and / or do not contain TeO2; and / or do not contain clarifiers, and the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3, and the clarifier is one or more of Sb2O3, SnO2, and CeO2.

19. The optical glass according to any one of claims 1 to 3, characterized in that: The refractive index n of the optical glass d 1.86 to 1.93, preferably 1.87 to 1.92, more preferably 1.88 to 1.91; Abbe number ν d It is 16-24, preferably 17-23, and more preferably 18-22.

20. The optical glass according to any one of claims 1 to 3, characterized in that: The thermal expansion coefficient of the optical glass is α 100 / 300℃ 95×10 -7 / K or less, preferably 90×10 -7 / K or less, more preferably 85×10 -7 / K or less; and / or acid resistance stability D A 2 or more, preferably 1; and / or water resistance stability D W Two or more types, preferably one type; and / or relative partial dispersion P g,F 0.58 to 0.72, preferably 0.60 to 0.68, more preferably 0.63 to 0.66; and / or relative partial dispersion deviation value ΔP g,F is 0.08 or less, preferably 0.01 to 0.06, more preferably 0.02 to 0.05; and / or the transition temperature T g 670°C or less, preferably 660°C or less, more preferably 650°C or less; and / or abrasion degree F A 230 to 270, preferably 240 to 265, more preferably 245 to 260; and / or density ρ is 3.90 g / cm 3 Below, preferably 3.80g / cm 3 Below, more preferably 3.70g / cm 3 Below; and / or 70 440nm or less, preferably λ 70 430nm or less, preferably λ 70 is 425nm or less; and / or λ5 is 400nm or less, preferably λ5 is 390nm or less, more preferably λ5 is 385nm or less; and / or weather resistance CR is 2 or more, preferably 1; and / or Young's modulus E is 8000×10 7 Pa or more, preferably 9000×10 7 Pa or more, more preferably 9500×10 7 Pa or more; and / or the bubble degree is A grade or more, preferably A0 grade or more, more preferably A 00 class.

21. A glass preform, characterized in that: Made of the optical glass described in any one of claims 1 to 20.

22. An optical element, characterized in that The optical glass is made of the optical glass described in any one of claims 1 to 20, or the glass preform described in claim 21.

23. An optical instrument, characterized in that A method of manufacturing an optical device comprising the optical glass according to any one of claims 1 to 20, or comprising the optical element according to claim 22.

Citation Information

Patent Citations

  • Optical glass, optical elements and preformed articles for precise pressurization shaping

    CN101792258A

  • Optical glass

    CN1204073C